2014
DOI: 10.5897/ajar2013.7525
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and phosphorus uptake by wheat as influenced by long-term phosphorus fertilization

Abstract: Phosphate reactions in the soil have important implications for crop growth and its nutrition to plants. Using a 40 years old long-term fertility experiment, we studied the fate of different sources of applied P into its nutrition to wheat in calcareous soils in a pearl millet-wheat cropping system during rabi 2009 and 2010. Results showed that water soluble sources of phosphatic fertilizers (Single super phosphate, Diammonium phosphate, Urea ammonium phosphate) were found superior over partially water soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Because nutrient uptake was calculated from their concentrations and corresponding dry leaf yield. These results are in agreement with the results found by Sushanta et al, (2014), who found that the total P uptake by wheat increased with increasing P fertilizer application.…”
Section: Leaf P Concentration and Uptakesupporting
confidence: 83%
“…Because nutrient uptake was calculated from their concentrations and corresponding dry leaf yield. These results are in agreement with the results found by Sushanta et al, (2014), who found that the total P uptake by wheat increased with increasing P fertilizer application.…”
Section: Leaf P Concentration and Uptakesupporting
confidence: 83%
“…Kpongor (2007), Arthur (2009) and Adiku et al (2009). The influence of P nutrition on the growth of maize in Kenya was reported by Delve et al (2009), sorghum in semi-arid region in Ghana by MacCarthy et al (2009) and in wheat in India by Saha et al (2014). In this study, N was the most limiting soil nutrient as it is required in larger amounts than any other nutrient.…”
Section: Grain Yieldmentioning
confidence: 55%
“…Use of phosphorus fertilizers had a beneficial effect on phosphorus use efficiency (Ghafoor, 2016). However, the choice of phosphorus fertilizer type is essential because the reaction of added P after dissolution decides its availability to the crop growth and fertilizer use efficiency (Sushanta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%